Efeitos de cargas não-lineares no dimensionamento de transformadores trifásicos de distribuição - SANTOS, Cairo Rezende dos (2012)
The intense use of solid state converters that use semiconductor in processing electric power of electrical and electronic equipment brings great benefits such as lower cost, greater efficiency and comfort, but also brings disadvantages, because when connected to the distribution system of electricity produced currents distorted relative to the sinusoidal waveform.. Thus also cause nonsinusoidal voltages that produce additional losses in conductors, transformers and also in its own equipment that generated them. In transformers feeding nonlinear loads occur further losses, which increase the temperature and compromising the insulation life. The factors used and internationally recommended in UL 1561-1994 (K-factor) and IEEE Std C57.110-2008 (Harmonic Loss Factor - FHL) to calculate maximum power three-phase transformers operating in these conditions will be objects of comparison. This work, performed in the laboratory with two three-phase transformers connected in the configuration back-to-back, aims to conduct a survey of actual losses in transformers under linear and nonlinear load and also propose a new scale factor that the three-phase transformers feeding these specific charges. Another aspect to be addressed is planning the design of transformers using these factors. The measurements and data processing are performed at low voltages of the transformers and use transducers voltage and current with high accuracy and LabVIEW programming.